2013
DOI: 10.1021/cb400265y
|View full text |Cite
|
Sign up to set email alerts
|

Features of Modularly Assembled Compounds That Impart Bioactivity Against an RNA Target

Abstract: Transcriptomes provide a myriad of potential RNAs that could be the targets of therapeutics or chemical genetic probes of function. Cell permeable small molecules, however, generally do not exploit these targets, owing to the difficulty in the design of high affinity, specific small molecules targeting RNA. As part of a general program to study RNA function using small molecules, we designed bioactive, modularly assembled small molecules that target the non-coding expanded RNA repeat that causes myotonic dystr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 67 publications
(213 reference statements)
0
49
0
2
Order By: Relevance
“…(67, 68) Indeed, the affinity and selectivity of a multivalent compound that targets RNA is controlled by the nature of the scaffold that displays the RNA-binding modules, valency, and the distance between RNA-binding modules. (36, 47, 69)…”
Section: Resultsmentioning
confidence: 99%
“…(67, 68) Indeed, the affinity and selectivity of a multivalent compound that targets RNA is controlled by the nature of the scaffold that displays the RNA-binding modules, valency, and the distance between RNA-binding modules. (36, 47, 69)…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was then incubated with the beads, and RNAs that bound the small molecule were identified by qRT-PCR. Indeed, this approach was used to confirm that small molecules can be designed to bind a desired target (18, 79). In one study, we showed that a small molecule designed to bind the r(CGG) repeat that causes FXTAS pulls down more of the desired target than an oligonucleotide complementary to the repeat (18).…”
Section: Methods For Target Validation Of Small Moleculesmentioning
confidence: 99%
“…If RNAs cause disease by sequestering protein, as in the case of DM1, then the small molecule could displace RNA-bound protein in cellulo or in vivo and improve cellular defects caused by sequestration. Indeed, monomeric and multivalent compounds have been developed against the RNAs that cause DM1, DM2, c9ALS/FTD, and fragile X-associated tremor ataxia syndrome (FXTAS) (18, 78, 79). In general, bioactive compounds improve disease-associated defects in cellulo in the low- to mid-micromolar range (18, 78, 79).…”
Section: Development Of Strategies To Design Small Molecules To Targementioning
confidence: 99%
“…3 [26] se realizó una minimización de energías para la estructura MBNL-1, usando el método de "steepest descent", seguidamente se tomó la estructura minimizada de la MBNL-1 y se procedió a realizar la Dinámica Molecular, agregándole condiciones periódicas de contorno (PBC) [27] usando la funcional CAMB3LYP [28], la cuál es una funcional híbrida de intercambio correlación que combina las cualidades híbridas del B3LYP y una corrección de largo alcance. Además de la funcional CAMB3LYP, se utilizó el set de base TZVP para obtener una convergencia más rápida y mejor de las energías y geometrías a nivel de DFT (Density Theory Function) [29] y así evitar las frecuencias negativas al momento de la optimización.…”
Section: B Optimización De Las Estructuras Mediante Mecánica Moleculunclassified
“…5. Dichos aminoácidos logran interaccionar con los nitrógenos presentes en la espermidina logrando obtener sitios favorables de interacción con la estructura del fosfodiéster cargada negativamente en el ligando [28]. Revista TECNIA Vol.27 N°1 Enero-Junio Tabla 1.…”
Section: Acoplamiento Molecular Entre El Mbnl-1 Y Launclassified